Oxygen detection system based on TDLAS–WMS and a compact multipass gas cell. Issue 5 (11th March 2022) - Chang, Jvqiang; He, Qixin; Li, Jiakun; Feng, Qibo
Abstract: In this paper, a sensitive oxygen monitoring system was demonstrated using tunable diode laser absorption spectroscopy and wavelength modulation spectroscopy. Light from a distributed feedback laser near 760.8 nm was coupled into a compact Herriott cell with a 3.3 m optical path. A LabVIEW‐based orthogonal lock‐in amplifier was developed to extract the gas concentration information from the absorption signal, which can achieve baseline fitting, background deduction, filtering, and harmonic extraction. Oxygen measurement experiments were conducted, and the performance of the system was obtained. Based on an Allan deviation analysis, the minimum detection limit of the system was 0.247% at an averaging time of 1 s and could improve to 0.022% when the averaging time was 40 s.